The Oxford handbook of light in archaeology - Moyes, Holley; Papadopoulos, Costas (Oxford handbooks., 2022)
Light has a fundamental role to play in our perception of the world. Natural or artificial lightscapes orchestrate uses and experiences of space and, in turn, influence how people construct and negotiate their identities, form social relationships, and attribute meaning to (im)material practices. 0Archaeological practice seeks to analyse the material culture of past societies by examining the interaction between people, things, and spaces. As light is a crucial factor that mediates these relationships, understanding its principles and addressing illumination's impact on sensory experience and perception should be a fundamental pursuit in archaeology. However, in archaeological reasoning, studies of lightscapes have remained largely neglected and understudied. This volume provides a0comprehensive and accessible consideration of light in archaeology and beyond by including dedicated and fully illustrated chapters covering diverse aspects of illumination in different spatial and temporal contexts, from prehistory to the present. Written by leading international scholars, it interrogates the qualities and affordances of light in different contexts and (im)material environments, explores its manipulation, and problematises its elusive properties. The result is a synthesis of invaluable insights into sensory experience and perception, demonstrating illumination's vital impact on social, cultural, and artistic contexts.